Climatic and geological drivers of diversity in Iranian Barbels lineage (Cypriniformes: Cyprinidae: Barbinae and Torinae): An integrative taxonomic perspective - Hadi Khoshnamvand; Asghar Abdoli; Faraham Ahmadzadeh; Karel Janko (PLoS ONE, 2026)
Iranian Barbel taxonomy and evolutionary history (Cyprinidae: Barbinae and Torinae) remain contentious due to overlapping morphological traits and limited molecular data. This study applies an integrative taxonomic framework to elucidate species boundaries, phylogenetic relationships, and the environmental drivers of diversification within Barbels lineages across Iran. We analyzed mitochondrial DNA ( Cytb and COI genes), seven meristic morphological characters, and five spatial environmental predictors from specimens collected across localities representing major Iranian basins. Phylogenetic reconstructions using Maximum Likelihood and Bayesian Inference revealed three main monophyletic groups: (1) Arabibarbus , Mesopotamichthys , and Carasobarbus (Torinae); (2) Luciobarbus ; and (3) Barbus sensu stricto (Barbinae). Principal Component and Canonical Variate Analyses of meristic data corroborated molecular findings, supporting the delineation of this taxa. Ecological Niche Evolution analysis indicated several species occupy similar climatic niches, suggesting parallel evolutionary responses to environmental pressures. Divergence time estimates and lineage-through-time analyses linked major cladogenic events to regional orogeny and Quaternary climatic fluctuations. Species delimitation analyses suggested potential synonymy among specific taxa (e.g., L. capito with L. conocephalus ; L. esosinus with L. xanthopetrus ), highlighting the need for taxonomic revision. Our integrative approach demonstrates that geological history and climatic factors have shaped the diversity and distribution of Barbels in Iran. These findings provide a robust framework for future taxonomic, conservation, and biogeographic studies of Iranian freshwater fishes.